The Effectiveness of Problem-Based Learning Model in Improving Students' Critical Thinking Skills in Biotechnology Material - Halimatus Sadiah, Siti; Sarwo Danuji; Hanif Rafika Putri (BIOEDUKASI: Jurnal Biologi dan Pembelajarannya, 2025)
Students must possess the essential 21st-century skill of critical thinking, especially in the study of biotechnology, which includes more complicated subject matter and contextual topics like GMOs and bioethics. The use of traditional learning methods, which are still the norm, is less effective in fostering these skills because there is little student participation. Problem-Based Learning (PBL) is an innovative solution that emphasizes real-world problem-based learning that is both collaborative and exploratory. The purpose of this study is to determine how well the PBL model improves students' critical thinking skills in biotechnology topics. The study, which included two XI IPA classes at Satya Dharma Jember High School, employed a quantitative approach with a quasi-experimental design (pretest-posttest control group design). The experimental class (32 students) received PBL-based education, while the control class (32 students) received instruction using traditional methods. A test of critical thinking skills based on Ennis' indicators is the tool utilized. The findings revealed a notable improvement in both groups, with the experimental group scoring higher (24.50 points) than the control group (12.25 points). The paired sample t-test revealed a notable improvement (p < 0.05), while the independent sample t-test showed a significant difference between the groups (t = 4.78; p = 0.000). According to this study, PBL is successful in fostering critical thinking skills because it provides an active, contextual, and reflective learning experience. As a result, PBL is advised as a learning technique for subjects like biotechnology that require critical thinking.